Development of a composite drought indicator for operational drought monitoring in the MENA Region - Bergaoui, Karim; Belhaj Fraj, Makram; Fragaszy, Stephen; Ghanim, A.; Hamadin, O.; Al‑Karablieh, E.; Al‑Bakri, J.; Fakih, M.; Fayad, A.; Comair, F.; Yessef, M.; Mansour, H. B.; et al. (Nature Portfolio, 2024)
This paper presents the composite drought indicator (CDI) that Jordanian, Lebanese, Moroccan, and Tunisian government agencies now produce monthly to support operational drought management decision making, and it describes their iterative co-development processes. The CDI is primarily intended to monitor agricultural and ecological drought on a seasonal time scale. It uses remote sensing and modelled data inputs, and it reflects anomalies in precipitation, vegetation, soil moisture, and evapotranspiration. Following quantitative and qualitative validation assessments, engagements with policymakers, and consideration of agencies’ technical and institutional capabilities and constraints, we made changes to CDI input data, modelling procedures, and integration to tailor the system for each national context. We summarize validation results, drought modelling challenges and how we overcame them through CDI improvements, and we describe the monthly CDI production process and outputs. Finally, we synthesize procedural and technical aspects of CDI development and reflect on the constraints we faced as well as trade-offs made to optimize the CDI for operational monitoring to support policy decision-making—including aspects of salience, credibility, and legitimacy—within each national context.